Peningkatan Hasil Belajar Peserta Didik Menggunakan Model Problem-Based Learning di Kelas V Sekolah Dasar - Putra, Aditya; S, Farida (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2023)
This research is based on the lack of orienting students on real problems that exist around them. So that students cannot understand the concepts studied independently. The purpose of this study is describe to increase student learning outcomes in integrated thematic learning using problem-based learning (PBL) models in class VB SDN 10 Bandar to Padang city. This research is a classroom action research using qualitative and quantitative approaches. It was carried out in two cycles, covering four stages, namely planning, implementing, observing and reflecting. The data in this study are lesson plans, implementation of learning and student learning outcomes. The subjects of this study were teachers and students with a total of 24 students. The results of the research on the observed aspects experienced an increase, namely: a) lesson plans for the first cycle 87.49% (B), in the second cycle it became 97.22% (SB). b) the teacher aspect of cycle I 82.14% (B), in cycle II that is 92.85% (SB), c) student aspects of the cycle I 82.14% (B), in cycle II that is 92.85%, (SB). Student learning outcomes in cycle I was 73% (C), in cycle II with an average of 85.06 (B). Thus, the learning outcomes of students in integrated thematic learning increased by using the PBL model.